Atrioventricular re-entrant tachycardia and atrioventricular node re-entrant tachycardia in a patient with cancer under chemotherapy: a case report and literature review - Dai, Meiyan; Chen, Yue; Qin, Jin (Frontiers in Cardiovascular Medicine, 2024)
Cardio-oncology is a new field of interest in cardiology focusing on the detection and treatment of cardiovascular diseases, such as arrhythmias, myocarditis, and heart failure, as side-effects of chemotherapy and radiotherapy. The association between chemotherapeutic agents and arrhythmias has previously been established. Atrial tachyarrhythmias, particularly atrial fibrillation, are most common, but ventricular arrhythmias, including those related to treatment-induced QT prolongation, and bradyarrhythmias can also occur. However, the association between chemotherapeutic agents and atrioventricular re-entrant tachycardia (AVRT)/atrioventricular node re-entrant tachycardia (AVNRT) remains poorly understood. Here, we report a patient with new-onset AVRT/AVNRT and lung cancer who underwent chemotherapy. We considered that chemotherapy or cancer itself may have been a trigger for the initiation of paroxysmal AVRT/AVNRT, and that radiofrequency catheter ablation was effective in treating this type of tachycardia. Here, possible mechanisms and potential genes (mostly ion channels) involved in AVRT/AVNRT are summarized and the mechanisms underlying the possible regulatory patterns of cancer cells and chemotherapy on ion channels are reviewed. Finally, we considered that ion channel abnormalities may link cancer or chemotherapy to the onset of AVRT/AVNRT. The aim of the present study was to highlight the association between chemotherapeutic agents and AVRT/AVNRT and to provide new insights for future research. Understanding the intermediate mechanisms between chemotherapeutic agents and AVRT/AVNRT may be beneficial in preventing chemotherapy-evoked AVRT/AVNRT (and/or other arrhythmias) in future.